The original : a novel - Stevens, Nell, 1985- (W.W. Norton & Company, 2025)
Raised on the fringes of her uncle's crumbling Oxfordshire estate, gifted art forger Grace plots her escape until the arrival of a man claiming to be her long-lost cousin forces her to confront shifting boundaries of identity and truth.